DEVELOPING ENGLISH SPEAKING MATERIALS OF DESCRIPTIVE TEXT FOR GRADE X STUDENTS OF CULINARY STUDY PROGRAM AT SMK NEGERI 10 MEDAN - Novita Sari Hasibuan; Rahmad Husein; Maya Oktora (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2019)
This research has aims to develop English speaking materials for grade X culinary study program at SMKN 10 Medan, first this research was conducted by Research and Development through has Six stages, they are: gathering information and data, analyzing data, designing new materials, validating by the experts, revising and the last was Final product. The subject in this research was students grade X boga 3 at SMKN 10 Medan where the students consisting of 36 students, the instrumentations for data collection  were giving a questionnaire and interview, questionnaire was administrate and it answer by the students to get the students need, and the interview was administrate to the English teacher, the result of the questionnaire and interview prove that the student need some appropriate speaking material in descriptive text that has relation with their program study, that is culinary. Thus, developing English speaking materials consist of three units: lets’ talk about chef Juna (describing People), how the smell, taste and texture of your favorite food? (Describing things) and the last units was talk about famous restaurant (Describing Place). The product has been validated by two experts, and the average score are 4, 75 are coming from English Lecture’s, the second average score 4, 89 are coming from English teacher. From the score above, it means that the product categorized as relevant for grade X students of culinary study program.Key words: R&D, English for Specific Purposes, English speaking materials, culinary study program.